(untitled) (Economics and region, 2021)
Impact of the current economic, financial crisis and the coronavirus pandemic on the business activities of companies are very huge and unpredictable. The traditional audit in the form of a total verification of primary documents has proved ineffective. The auditor’s world is still grappling with how to ensure the most effective approach to organize their work. Risks are the main vector to which the auditor should pay attention. Risk identification, classification and assessment procedures are investigated in the article. Author has expressed opinion that risk management is fundamental to the success of organizations in every business sector. This is the complex world, full of uncertainty, so whatever its size, it must manage risk. Risk-based audit and assessment is a good chance and a modern way of understanding different threats that an organization faces. Recommendations on a new auditors’ approach that should help get a rational and pragmatic view of risk are developed.